A proposed guide to reducing bias and improving assessments of decolonization in global health research - Ngaruiya, Christine; Muhammad, Muzzammil Imran; Sam-Agudu, Nadia A. (Frontiers in Education, 2024)
We leverage the "Inner Setting" and "Outer Setting" domains of the Consolidated Framework for Implementation Research (CFIR), a well-established, commonly-used implementation science framework to critically assess the status quo of decolonization and to develop criteria to help guide decolonization efforts in academic contexts. We defined the Inner Setting as academic and research institutions leading and participating in global health research collaborations, and the Outer Setting as the funding, editorial, and peer review policies and practices that influence knowledge production in global health. Research institutions in the Inner organizational domain continually interact with the Outer policy domains. We categorize the levels at which decolonization may occur and where action should be focused as follows: 1) North-South, 2) South-South, 3) Local South, and 4) Local North (2). Using CFIR domains and the levels of action for decolonization, we propose a multi-level guide to improve on the standardization, granularity, and accuracy of decolonization assessments in global health research.The proposed guide is informed by our global health research expertise and experiences as African scientists with extensive exposure in both global North and global South research contexts. We expect that the proposed guide will help to identify and address the biases identified and will lead to better knowledge-driven action in the process of decolonizing global health research.